Um retrato em preto e branco da Associação Atlética de Sergipe: por entre as sombras do projeto republicano (1925-1949) - Silva, Néviton Felipe da (2013)
The Athletic Association of Sergipe was an institution created as one of the elements that has been serving the interests of the political-ideological deployed by the Republican government in the early twentieth century. However, this assertion was based on some evidence that over study were being revealed. The overall goal of the work, which was a critical analysis of educational practices, cultural representations that have been reproduced and incorporated by this institution during the study period, gave us the opportunity to confirm the initial hypothesis. However, to reach this definition was necessary to walk in other dimensions that were submerged in the time and origin of the problem statement. The first dimension tried to give an overview of the changes in political, economic and social development of Brazil brought about by the advent of the establishment of the Republic and its possible consequences in the context Sergipe where this institution was created. The second dimension opted to try to understand the historical aspects that conceptualized and formed a functional and organizational framework of voluntary associations in Brazil and worldwide, as well as factors related to the field of their various assignments. Given the facts, we find that the offer to elite Aracaju, as a place of entertainment, leisure and above all strengthening consolidation of social relations, the Athletic Association of Sergipe just fulfilling its role of disseminating agent of the Republic.